Benign cutaneous ancient schwannoma masquerading as well differentiated nerve sheath tumor: a case report - Ganesan, Swaminathan; Subramani, Balakrishnan (International Surgery Journal, 2019)
Ancient schwannomas are a rare entity of benign cutaneous nerve sheath tumor in patients without von Recklinghausen disease. Head and neck, mediastinal, retroperitoneal ancient schwannomas have been reported and has high degree for malignant transformation. Ancient schwannoma of the peripheries have been reported in only few cases and in hand only two cases have been reported. We present this case for its rarity and the diagnostic dilemma occurring with FNAC. Thus these tumors if present in periphery and in non-neurofibromatosis patient can masquerade as malignant tumors but still can safely are treated with excision biopsy alone and with almost nil recurrence.